Weighted p-majorization and Stable vector: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this paper we generalized the notion of weighed p− majorization for any two vectors in Rn. Wealso define stable vector for a given set of vectors. Then we prove existence of stable vector for n = 2.And finally we give some conditions on a set of vectors for existence of stable vector for n ≥ 3. we alsogive some examples for illustration our theorems.